Barriers and enablers for accessing rehabilitation services: findings from the rehabilitation choices study, part 1—healthcare professionals' perspectives - Hodyl, Nicolette (2024)
Introduction: Globally, there is an increasing demand for quality medical rehabilitation services. This is the first article of a two-part series showing the findings from the Rehabilitation Choices study in which the main aim was to understand the current landscape of decision-making, enablers and barriers to access appropriate rehabilitation services in the Australian setting. In Part 1, these insights were sought from a healthcare professionals' perspective. Methods: This was an exploratory, qualitative study, using semi-structured interviews with a discussion guide that was codesigned together with rehabilitation clinicians and rehabilitation researchers. Themes and sub-themes were identified using an inductive approach. Results: We interviewed a heterogeneous group of 31 professionals who are involved in making referral decisions about rehabilitation or who design and deliver rehabilitation programs, including specialist rehabilitation physicians and other medical doctors across in-patient, outpatient, and primary care settings, allied health professionals, rehabilitation service managers, nurses, multicultural health liaison officers and rehabilitation research scientists. Three key themes relevant to barriers and enablers to service access were identified from the data: defining rehabilitation; a lack of timely access to patient and rehabilitation service data; and patient diversity not expected by the system. Conclusions: Healthcare professionals who make decisions about rehabilitation referrals and services feel that it was necessary for them to keep up to date with information relating to rehabilitation services. There was some concern regarding what rehabilitation constituted and what services were available for different clinical indications. They also indicated that current systems did not consider diversity among patients' needs and goals. Their recommendations included the need for better communication pathways, improved referral systems and resources that could help provide best practice of rehabilitative care in the future. Patient or Public Contribution: Three study team members had a lived experience of rehabilitation as a patient or carer, and previous experience participating in qualitative research. They worked with the study team to codesign the recruitment strategy, participant-facing communications, the interview discussion guide, and the approach to the conduct of activities with participants and in the interpretation and contextualization of findings and all were involved in writing this manuscript.